Historic precedent of the Education in Costa Rica: From the colony to the beginning of the “School of Dentistry”, Universidad de Costa Rica - Hernández Rivera, Patricia (2014)
Education in Costa Rica had a poor beginning, due to poverty and being far away from the “Capitania General de Guatemala”, so there were few educational opportunities. During the XIX century the “Universidad de Santo Tomas” was created, but was closed soon thereafter during the Educational Reform of 1886. Dentistry was practiced empiricaly and later on foreign trained dentists began to arrive in the country whom incorporated to the ̈Facultad de Medicina, Cirugía y Farmacia ̈. Disputes between professional and empirically trained dentist began to arise as the professionals argued the need for knowledge based treatment, while the empirically trained insisted on being allowed to practice and recognized as professionals, especially since there was no way young people could train professionally as dentists at that time. In 1940, during Dr. Rafael Ángel Calderón Guardia ́s presidency, the “Universidad de Costa Rica” was created with the objective of giving the country cultural and scientific knowledge. A year later, the “Facultad de Cirugía Dental” was created and opened on March 16, 1942 with 64 students, in a borrowed building and minimal furniture.